Implementation of the Values of Disciples of Christ in Inclusive Education at Ambon Christian High School - Imanuela Pandu (Electronic Journal of Education, Social Economics and Technology, 2025)
Ambon Christian High School (SMA Kristen Ambon) is the first driving school to implement an inclusive learning system by raising the theme of learning learning for everyone, so that Ambon Christian High Schools receive 7 children with special needs who learn together with other students. In addition to implementing a standard curriculum there is also a plus curriculum which is a superior program in character education through the Dishcipels of Christ program as an effort to instill Christian values to students in Ambon Christian High School. The research used is qualitative research or field research where through observation and interviews to obtain in -depth and accurate information for further the data is processed and compiled into sentence by sentence that explains the object of research. The results obtained in this study, that the curriculum program plus discipels of christ has a positive impact on the growth of knowledge, character and faith of Ambon Christian High School students, especially for growth for students with special needs in schools.